Lyme borreliosis incidence in relation to mammalian abundance, climate, and landscape characteristics in a boreal area - Aminikhah, Mahdi; Aalto, Juha; Forsman, Jukka T.; Gregow, Hilppa; Henttonen, Heikki; Huitu, Otso; Kajanus, Mira H.; Korpimäki, Erkki; Lindén, Andreas; Ollgren, Jukka; Pietiäinen, Hannu; Sane, Jussi; et al. (BioMed Central, 2026)
Background: The circulation of tick-borne pathogens is influenced by the availability of ticks, the hosts of ticks and pathogens, and the environmental conditions that affect both the ticks and their hosts. Lyme borreliosis (LB), caused by Borrelia burgdorferi sensu lato and transmitted by Ixodes spp. ticks, is the most common tick-borne disease in the Northern Hemisphere. Understanding the spatio-temporal dynamics of human LB incidence regarding abundance of ticks and hosts and environmental factors is essential for effective disease risk management. Methods: We analyzed long-term (1997–2018) and spatially extensive (277 municipalities covering 230,000 km2) data on human LB incidence in Finland. Using dynamic species distribution models, we assessed the effects of (i) the abundance of pathogen reservoir hosts used by immature ticks (voles and squirrels), (ii) abundance of the key reproductive hosts for adult ticks (moose and deer), (iii) landscape characteristics, and (iv) climatic variables on the risk of LB. Results: LB presence and incidence varied across the study area and exhibited a clear increasing trend. While host species showed temporal and regional variation in abundance, their relationships with LB risk were inconsistent. In contrast, environmental variables showed more consistent patterns: increased forest fragmentation, longer growing seasons, and higher humidity were generally associated with elevated LB risk. Conclusions: Our study suggests that the factors explaining LB epidemiology cannot be generalized spatially but depend on local climate, landscape, and host community. Given the available data, environmental conditions seem to play a more predictable role in LB epidemiology than the estimated abundances of hosts at the municipality level, yet we cannot exclude host abundance effects. Hence, the key to enhancing our understanding of the complex mechanisms underlying the epidemiology of LB and other tick-borne infections is to clarify how tick distribution and abundance respond to alterations in the host community, habitat features, and local climate.
Keywords: zoonotic disease; tick-borne disease; reservoir hosts; Borrelia burgdorferi sensu lato; Ixodes spp.; species distribution models